Correlation between Parathyroid Hormone Serum Levels andAbdominal Aortic Calcification in Chronic Hemodialysis Patientsat Dr. Mohammad Hoesin Center General Hospital Palembang - Akbar, M Yusuf Arief; Ali, Zulkhair; Indrajaya, Taufik; Suhaimi, Novadian; Devi, SNA Ratnasari; Bahar, Erial (Jurnal Penyakit Dalam Indonesia, 2021)
Introduction. Cardiovascular disease is the most common cause of death in patients with chronic kidney disease (CKD). This is evidenced by the finding of vascular calcification in CKD patients. The process of vascular calcification that occurs is often associated with secondary hyperparathyroid conditions that are complications of CKD patients. The aim of this study was to asses the relationship between serum PTH levels and the abdominal aorta calcification (AAC) in CKD patients undergoing hemodialysis (HD) Methods. This observational analytic study with cross-sectional correlation test was conducted in the internal medicine ward of dr. Mohammad Hoesin Palembang from July to December 2019. Subjects were patients who had undergone HD >3 months with age >18 years. All subjects were examined for serum PTH levels and measured the carotid artery wall using doppler ultrasonography and the degree of calcification of the abdominal aorta using a lateral lumbar X-ray which was calculated using the Kauppila score. Results. There were 86 of HD patients studied, 65 subjects (75.6%) had high serum PTH levels and 46 subjects (53.5%) who had AAC. The Spearman correlation analysis showed that serum PTH levels had a relationship with Kauppila score (p=0.014, r=0.264). Multivariate linear regression analysis obtained age (p<0.001, r=0.510), duration of HD (p=0.020, r=0.256), history of hypertension (p=0.031, r=0.239) and serum phosphate levels (p=0.011, r=0.281) had a relationship to the Kauppila score. Conclusions. There is a significant relationship between serum PTH levels and AAC in chronic HD patients. The presence of factors including age, duration of HD, hypertension, and serum phosphate levels also affect the incidence of AAC